The prevalence and the associate factors for thyroid malignancy in large goiters results from six years’ experience in Hospital Raja Perempuan Zainab II - Yah Wui, Choo (2015)

(untitled)
Background: Large goiters are very common and it is frequently encountered by endocrine surgeons especially in developing countries. Rarely, issues regarding large goiters have been discussed, particularly the association between large goiter and thyroid cancers. The objectives of this study are to analyze the associate factors of thyroid malignancy in large goiters as well as the surgical complications in performing resection for large goiters. Methods: Patients who had primary thyroid surgery between June 2007 and May 2013 were retrospectively reviewed. Patients who underwent thyroidectomy with a resected specimen of ≥ 50g in hemithyroidectomy or ≥ 100g in total thyroidectomy were recruited in the study. The associate factors for thyroid cancer in large goiters (age, gender, thyroid function status, compression symptom and, nodularity) were analyzed. The surgical complications namely temporary hypocalcaemia, permanent hypoparathyroidism, RLN injury, post-operative haemorrhage, surgical site infection, local structures injury and mortality associated with thyroid surgery were recorded. Results: A total of 611 patients who had capsular dissection thyroid surgeries were recruited in the study. The prevalence of large goiter was 410 (67.1%) and the prevalence of thyroid malignancy in large goiters was 115 (28.0%). The patients with large goiters had higher chance to have thyroid malignancies with OR of 1.52 (1.02, 2.28). Multiple Logistic Regression Analysis revealed that the significant associate factors for thyroid malignancy in large goiters were age and STN with OR of 1.02 (1.01, 1.04) and 1.80 (1.10, 2.94), respectively. There were 82 (25.5%) temporary hypocalcaemia, 9 (2.8%) permanent hypoparathyroidism, 4 (1.2%) RLN injuries, 8 (2.5%) post-operative haemorrhages, 4 (1.2%) local structure injuries and 1 (0.3%) death after thyroid surgery for large goiters. Conclusions: The high prevalence of large goiters in the developing countries necessitates the different approach in the management of thyroid disease. Large goiters are associated with higher prevalence for thyroid malignancy. With the doubt of sensitivity in detecting thyroid malignancy from FNAC in large goiter, surgeons should consider removing the goiter early especially in older patients and those with STN. Nevertheless, the risks of surgery for large goiter should be deliberated and the surgery should only be performed by expert personal.